The Five Ws of the Water-Energy-Food Nexus: A Reflexive Approach to Enable the Production of Actionable Knowledge - Dalla Fontana, Michele; Wahl, Darin; Moreira, Fabiano de Araujo; Offermans, Astrid; Ness, Barry; Malheiros, Tadeu Fabrício; Di Giulio, Gabriela Marques (Frontiers in Water, 2021)
The water-energy-food nexus is now a popular approach in the sustainability field. However, whereas the nexus calls for more holistic, inter- and transdisciplinary approaches, the research produced over the past decade has been fragmented and specialized. Furthermore, there is still a gap between the nexus as a descriptive and analytical concept and its operationalization. Nexus research needs a shift from ‘thinking’ to ‘action’, which we understand as the production of actionable knowledge. This paper delves into the literature and presents five ‘W’ questions as an iterative heuristic for the nexus concept to encourage reflexivity and inter-and transdisciplinary dialogue, while aiming at the production of actionable knowledge. We draw on the literature to discuss the five ‘W’ questions of the nexus, namely: i) Why, in which we explore the purpose of nexus research for actionable knowledge; ii) What, in which we explore the material aspect of the nexus and the interactions between water, energy and food systems; iii) Where, in which we discuss issues of scale, interactions between scales, and the geographical context of the nexus; iv) When, in which we consider temporal dimensions of nexus research with a particular emphasis on intergenerational trade-offs, and v) Who, which focuses on nexus stakeholders and the importance of understanding issues of justice and equity. Finally, we discuss the connections and dependencies between the five Ws, reinforcing the importance for researchers to reflect on their decision-making and engage in inter- and transdisciplinary debate to enable nexus ‘action’.